Steady states of $Λ$-type three-level systems excited by quantum light in lossy cavities - Rose, H.; Tikhonova, O. V.; Meier, T.; Sharapova, P. (arXiv:2109.00842)
The interaction between quantum light and matter is being intensively studied for systems that are enclosed in high-$Q$ cavities which strongly enhance the light-matter coupling. However, for many applications, cavities with lower $Q$-factors are preferred due to the increased spectral width of the cavity mode. Here, we investigate the interaction between quantum light and matter represented by a $Λ$-type three-level system in lossy cavities, assuming that cavity losses are the dominant loss mechanism. We demonstrate that cavity losses lead to non-trivial steady states of the electronic occupations that can be controlled by the loss rate and the initial statistics of the quantum fields. The mechanism of formation of such steady states can be understood on the basis of the equations of motion. Analytical expressions for steady states and their numerical simulations are presented and discussed.

Spectrally multimode integrated SU(1,1) interferometer - Ferreri, Alessandro; Santandrea, Matteo; Stefszky, Michael; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine; Sharapova, Polina R. (Quantum)
Nonlinear SU(1,1) interferometers are fruitful and promising tools for spectral engineering and precise measurements with phase sensitivity below the classical bound. Such interferometers have been successfully realized in bulk and fiber-based configurations. However, rapidly developing integrated technologies provide higher efficiencies, smaller footprints, and pave the way to quantum-enhanced on-chip interferometry. In this work, we theoretically realised an integrated architecture of the multimode SU(1,1) interferometer which can be applied to various integrated platforms. The presented interferometer includes a polarization converter between two photon sources and utilizes a continuous-wave (CW) pump. Based on the potassium titanyl phosphate (KTP) platform, we show that this configuration results in almost perfect destructive interference at the output and supersensitivity regions below the classical limit. In addition, we discuss the fundamental difference between single-mode and highly multimode SU(1,1) interferometers in the properties of phase sensitivity and its limits. Finally, we explore how to improve the phase sensitivity by filtering the output radiation and using different seeding states in different modes with various detection strategies.

Managing spectral properties and Schmidt mode content of squeezed vacuum light using sum-frequency converter - Sukharnikov, Vladislav; Sharapova, Polina; Tikhonova, Olga (Optics & Laser Technology)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Komplexe Wörter richtig schreiben. Wortanalyse als Rechtschreibstrategie. - Lang, Susanne; Topalović, Elvira (In: Praxis Deutschunterricht)

Rechtschreibstrategien und Sprachstrukturen. - Noack, Christina; Topalović, Elvira (In: Praxis Deutschunterricht)

Reconfigurable quantum photonics with on-chip detectors - Gyger, S; Zichi, J; Schweickert, L; Elshaari, A.W; Steinhauer, S; Covre da Silva, S.F; Rastelli, A; Zwiller, V; Jöns, Klaus D.; Errando-Herranz, C

Engineering the Luminescence and Generation of Individual Defect Emitters in Atomically Thin MoS2 - Klein, J; Sigl, L; Gyger, S; Barthelmi, K; Florian, M; Rey, S; Taniguchi, T; Watanabe, K; Jahnke, F; Kastl, C; Zwiller, V; Jöns, Klaus D.; et al.

Quantum Teleportation with Imperfect Quantum Dots - Basso Basset, F; Salusti, F; Schweickert, L; Rota, M.B; Tedeschi, D; Covre da Silva, S.F; Roccia, E; Zwiller, V; Jöns, Klaus D.; Rastelli, A; Trotta, R

Quantum dots as potential sources of strongly entangled photons: Perspectives and challenges for applications in quantum networks - Schimpf, C; Reindl, M; Basset, F.B; Jöns, Klaus D.; Trotta, R; Rastelli, A

Gate-Switchable Arrays of Quantum Light Emitters in Contacted Monolayer MoS2 van der Waals Heterodevices - Hötger, A; Klein, J; Barthelmi, K; Sigl, L; Sigger, F; Männer, W; Gyger, S; Florian, M; Lorke, M; Jahnke, F; Taniguchi, T; Watanabe, K; et al.